Application of backscattered electrons in detecting and profiling voids covered by self‐supporting metallic thin film. Issue 4 (12th February 2014) - Rajput, Nitul S.; Verma, H.C.
Summary Locating and profiling porosity or cavities in materials science has been of great interest and importance. However, it has been a great challenge to detect and analyze these hidden cracks because of lack of efficient measurement technique. Artificial voids are created and covered by self‐supporting thin films in order to replicate a hidden crack situation. Subsequently, these hidden voids are located in the scanning electron microscope images and the backscattered electrons, which emerge from a deeper part of a material and depend on the material property (such as atomic number, atomic density, etc.), are shown to play the key role in locating these hidden voids. Detection has been done by collecting the backscattered electrons as well as the secondary electrons (produced by the backscattered electrons). The efficacy of the detection technique is presented in terms of variation in the grayscale intensity values of the scanning electron microscope images. The role of the primary beam energy and the beam dwell time in the detection efficiency is discussed. The successful demonstration of the imaging technique in profiling hidden voids shows a promising and efficient analytical technique in detecting and analyzing invisible cracks in materials. SCANNING 36:430–436, 2014. © 2014 Wiley Periodicals, Inc.